Efectividad de dispersión de semillas por monos churucos (Lagothrix lagothricha) (2021)
Woolly monkeys (Lagothrix lagothricha) are among the largest frugivores in the Neotropics, and although their role as seed dispersers has been described, no research has evaluated their dispersal effectiveness (DE). In this study we used two approximations on the dispersal effectiveness for 15 species of plants consumed by woolly monkeys, using the information previously collected in the Tinigua National Park, Colombia including seed handling rates in focal trees, harvest duration per year and estimating the years in which the individuals of the species are adults (quantitative component). On the other hand, the probability of seed dispersal, germination rates, survival probabilities of seeds and seedlings during the first year in different types of forest (qualitative component) were taken into account and this information was complemented with data from Long-term plant survival from the literature.